2021
DOI: 10.1016/j.heliyon.2021.e06972
|View full text |Cite
|
Sign up to set email alerts
|

Hand washing practice among health care workers in Ethiopia: systemic review and meta-analysis, 2020

Abstract: Hand washing with soap and water is the single most weapon against infectious agents. Proper hand washing is not only reduces nosocomial infection, but also prevents the spread of current global concern Novel Corona viruses and other viral illnesses like cold and flu. Therefore, the aim of this study is to assess hand washing practice among health care workers in Ethiopia. Methods: In the current meta-analysis, the target variables search from different databases, like Google Scholar, African Journals OnLine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Single-population proportion formula was used to determine the sample by considering the proportion of good practice of standard precautions, 57.8% from previous study in Ethiopia, 9 95% confidence interval (CI), and margin of error of 5%. After adding a 5% non-response rate, the final sample size was 392.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-population proportion formula was used to determine the sample by considering the proportion of good practice of standard precautions, 57.8% from previous study in Ethiopia, 9 95% confidence interval (CI), and margin of error of 5%. After adding a 5% non-response rate, the final sample size was 392.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 In Ethiopia, only about half of the HCWs practiced appropriate standard precautions. [9][10][11] The studies identified the associated factors for the poor compliance of the HCWs to the SPs, including lack of infection control programs, lack of training, lack of knowledge and negative attitude towards SPs, inadequate management support, lack of supplies, crowded hospitals and excessive workloads. [12][13][14] Different initiatives were set globally and nationally to improve the wellbeing of patients, visitors, attendants, support staff, HCWs and general community in health care facilities, including Clean Care is Safer Care (WHO) and Ethiopian hospitals reform implementation guidelines (EHRG) aiming to improve quality of service and Clean and Safe Hospitals (CASH) aiming to make hospitals a clean, comfortable and safe environment for HCWs by Ethiopian government.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Washing hands properly can help prevent the spread and eliminate viruses on the surface of the hands that emerge after coughing, sneezing, and touching objects containing infectious pathogen. Handwashing also reduces the rate of respiratory infections and prevent them to enter the body or transmit (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have shown that attention to handwashing has been minimal among nursing staff. [ 19 ] Nalule et al . [ 20 ] demonstrated the importance of handwashing and hygiene of the medical staff in reducing the incidence of nosocomial diseases and disease transmission.…”
Section: Discussionmentioning
confidence: 99%